2021
DOI: 10.1093/eurheartj/ehab411
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intravenous ferric carboxymaltose on cardiac reverse remodelling following cardiac resynchronization therapy—the IRON-CRT trial

Abstract: Aims Iron deficiency is common in heart failure with reduced ejection fraction (HFrEF) and negatively affects cardiac function and structure. The study the effect of ferric carboxymaltose (FCM) on cardiac reverse remodelling and contractile status in HFrEF. Methods and results Symptomatic HFrEF patients with iron deficiency and a persistently reduced left ventricular ejection fraction (LVEF <45%) at least 6 months afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 33 publications
1
75
0
2
Order By: Relevance
“…Remarkably, in HFrEF patients receiving cardiac resynchronisation therapy (CRT), the presence of ID is associated with diminished reverse remodelling and lesser likelihood of functional improvement after CRT implementation, suggesting that adequate myocardial iron content is a prerequisite to derive optimal benefits from CRT implantation with respect to reverse cardiac remodelling and improved cardiac function [ 226 , 227 ]. In line with these findings, the recent IRON-CRT trial showed that IV iron repletion reverses myocardial remodelling and boosts cardiac performance and contractility in patients receiving CRT, which were also accompanied by improvements in quality of life and exercise capacity [ 62 ]. These results demonstrate the incremental potential of IV iron in reverse cardiac remodelling in addition to guideline-directed therapies that induce reverse remodelling [ 228 ].…”
Section: Deleterious Biological Consequences Of Iron Deficiencymentioning
confidence: 81%
See 1 more Smart Citation
“…Remarkably, in HFrEF patients receiving cardiac resynchronisation therapy (CRT), the presence of ID is associated with diminished reverse remodelling and lesser likelihood of functional improvement after CRT implementation, suggesting that adequate myocardial iron content is a prerequisite to derive optimal benefits from CRT implantation with respect to reverse cardiac remodelling and improved cardiac function [ 226 , 227 ]. In line with these findings, the recent IRON-CRT trial showed that IV iron repletion reverses myocardial remodelling and boosts cardiac performance and contractility in patients receiving CRT, which were also accompanied by improvements in quality of life and exercise capacity [ 62 ]. These results demonstrate the incremental potential of IV iron in reverse cardiac remodelling in addition to guideline-directed therapies that induce reverse remodelling [ 228 ].…”
Section: Deleterious Biological Consequences Of Iron Deficiencymentioning
confidence: 81%
“…Additionally, subgroup analysis of individual patient data meta-analysis ( n = 839) pooled from four double-blind, randomised controlled trials (RCTs) showed that although intravenous ferric carboxymaltose (FCM) generally reduces recurrent cardiovascular hospitalisations and cardiovascular mortality, patients with TSAT <20.1% benefit more from FCM iron than those with TSAT >20.1% even if ferritin levels were low [ 61 ]. Similarly, in the IRON-CRT trial, it was found that HF patients with TSAT <20% benefit more from FCM iron than if TSAT was >20% in terms of cardiac contractility and left ventricular ejection fraction (LVEF) [ 62 ]. However, similar interaction was not found in the AFFIRM-AHF trial [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the change in LVESV from baseline to follow-up was more pronounced in the ferric carboxymaltose group versus the standard of care group (−9.72 ml, 95% CI [−13.5, 5.93] versus −1.83 ml, 95% CI [−5.7, 2.1], p=0.001) However, the change in LVEDV was not different between the two treatment groups (ferric carboxymaltose: −2.5 ml, 95% CI [−5.3, 0.3] versus −1.9 ml, 95% CI [−4.7, 1.0], p=0.784). [ 43 ] Additionally, treatment with ferric carboxymaltose was capable of improving the force-frequency relationship as documented in Figure 5 . In patients treated with ferric carboxymaltose the negative force-frequency relationship was transformed into a positive force-frequency relationship.…”
Section: Effect Of Ferric Carboxymaltose On Cardiac Function and Stru...mentioning
confidence: 98%
“…Patients were randomised in a double-blind fashion to either standard of care (IV placebo) or ferric carboxymaltose. [ 43 ]…”
Section: Effect Of Ferric Carboxymaltose On Cardiac Function and Stru...mentioning
confidence: 99%
“…The main results of the IRON-CRT trial demonstrated that FCM improved LVEF, functional status, and exercise capacity in patients. 14 Of the 75 patients enrolled in the IRON-CRT trial, almost three out of four had RV dysfunction at baseline and over two thirds had RV dilatation. RV function was assessed via the RV fractional area change (RV FAC), tricuspid annular plane systolic excursion (TAPSE), and the pulsed tissue Doppler peak velocity at the RV lateral annulus (RV S ′ ).…”
Section: This Article Refers To 'The Effect Of Intravenous Ferric Car...mentioning
confidence: 99%